Carbon Financing and Community Forestry: A Review of the Questions, Challenges and the Case of Nepal - Staddon, Samantha (Journal of Forest and Livelihood, 2009)
Forestry-related ‘carbon-offsetting' projects are widely seen as the ideal solution to three equally challenging problems of the 21st century: climate change, biodiversity conservation and socio-economic development. Hopes are being pinned on the potential of Reducing Emissions from Deforestation and Degradation (REDD) schemes, which after 2012 will represent the most likely route for bringing the currently excluded community forests into official climate change mitigation. However, not everyone is convinced of their potential, and some point instead to the challenges involved in ensuring both environmental gains and livelihood benefits. This paper provides a background to carbon financing involving forestry, focusing on community forestry in the global South. It goes on to review a number of questions and challenges which affect the potential efficiency and equity of ‘carbon forestry'. Finally, it considers these issues with regard to community forestry in Nepal, arguing that they must be addressed in future policy or project development in the country. Key words: carbon financing, community forestry, REDD, biodiversity conservation, livelihoods Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.25-32